Pewujudan Tapis Digital FIR Pemilih Frekuensi Menggunakan DSK TMS320C6713 - Erwin, Gidion; Hidayatno, Achmad; Darjat, Darjat (Transmisi, 2010)
Digital frequency selector filter is the simplest application of digital signal processing, in which process only passing signal with specific desired frequency or band frequency. Digital frequency selector filter can be implemented as software or hardware. In this final project, frequency selector filter is implemented as hardware using DSK (Digital Signal Processor Starter Kit)  TMS320C6713. In this final project, designed three type of  frequency selector filter : Low Pass Filter (LPF), High Pass Filter (HPF), and Band Pass Filter (BPF) with filter length (N) and cut-off frequency (Fc) variation. Filter coefficient is the final product of design stage. FDATool Matlab is used to help filter design and filter coefficient calculation. Then, this filter coefficient is implemented as digital filter in DSK TMS320C6713 using CCS (Code Composer Studio) v.3.1. In CCS, it is also arranged some source code to initialize internal peripheral device on DSK TMS320C6713 (Codec, McBSP, etc), initialize interrupt mode, and initialize memory mapping. Based on experiment’s result, it’s known that the implemented’s magnitude response  approriate with FDATool’s magnitude response (frequency selector filter algorithm was successfully implemented in DSK TMS320C6713). However, gain’s value at pass band region is not exactly 0 dB because resistance losses from cables and the low precision of measurement device. Based on experiment’s result, it’s also known that filter with higher filter length produces better magnitude response characteristics, especially narrower transition width characteristic. Keyword :   digital signal processing, digital filter, frequency selector filter, DSK TMS320C6713.